Pengaruh Media Pop Up Book terhadap Keterampilan Berbicara Siswa MIS Al-Asriyah Langsa - Tesa ayu Ningsih; Chery Julida; Rita Sari (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2021)
The use of media is still limited to use in classroom learning, especially such as media pop up books because the work on this media is quite complicated. The purpose of this study was to find out the influence of pop up book media on speaking skills on the beautiful theme of togetherness of the proud sub-theme of being an Indonesian child in class IV MIS Al-Asriyah Langsa. The study used a quasi-experimental approach. From the analysis of data obtained the influence of pop up book media on the speaking skills of students speaking on the theme of the beautiful togetherness of the proud sub-theme of being an Indonesian child in class IV MIS Al-Asriyah Langsa. This is evidenced by the experimental grade practice average value of 14.9 with a standard deviation of 3.9 and a control class pretest average of 14.7 with a standard deviation of 4. After learning using pop up book media the average posttest class of the experiment increased to 18.35 with a standard deviation of 4.43. While learning in the control class without using learning media obtained a posttest value of 15.7 with a standard deviation of 4.1. From the results of the tcount test obtained a value of 8.36 and a ttable value of 2,042, it can be withdrawn from the influence of pop up book media on the speaking skills of MIS Al-Asriyah Kota Langsa students. rsquare was obtained by 0.546 or 54.6%. That means that the media pop up book has an influence on the speaking skills of students in class IV MIS Al-Asriyah Langsa with an influence rate of 54.6%.